Synthesis and Bio-Spectral Studies of Co(II) Complex of 5-Chloro-2,4-Dihydroxy Butyrophenoneoxime (CDHBOX) - Rehman, F.; Bhardwaj, M.; Jetley, U.K. (JOURNAL OF ADVANCES IN CHEMISTRY, 2010)
Co(II) complex of 5-chloro-2,4-dihydroxy butyrophenoneoxime (CDHBOX) was synthesized from 5-chloro-2,4-dihydroxy butyrophenoneoxime by using standard protocol, and characterized by elemental analyses, melting point determination and spectral data. The ML2Â (metal/ligand) stoichiometry of the complex was determined by spectrophotometric and potentiometric studies, and mass spectral data. The value of stability constant of the complex was found to be 6.94x 108Â while its standard free energy of formation is 12.155 kcal/mol at 27ÂºC. Beerâ€™s law is obeyed in the concentration range 2-15 ppm of Co. The value of molar extinction coefficient and sensitivity as per Sandellâ€™s scale were found to 3.35x 103 L.mol-1cm-1and 0.017 Î¼g Co/cm2Â respectively. The value of activation energy and the Arrhenius constant Arrhenius constant were found as 4.949 kjmol-1, 74.39. The IR studies reveal that the phenolic proton is lost on complexation and the oxygen of the phenolic (â€“OH) and nitrogen of the oximino (=NOH) groups coordinate with Co(II) ion. The electronic spectra and magnetic susceptibility measurement indicate that the complex is paramagnetic and tetrahedral in nature. The antimicrobial activity of different concentrations of ligand and its Co(II)-complex Â has been evaluated against Curvularia lunata, Fusarium oxysporum and Alternaria alternata fungi Â and Streproproteus, Staph, Escherchia coli, Klebsella, and pseudomonas bacteria. The results indicated that the ligand (CDHBOX) and its Co(II) complex have good anti-microbial properties.Â